Heavy Metal Stabilization in Agricultural Soils Using Biochar: Case Studies from European and Asian Agricultural Practices - Naheed Sharif; Talha; Muhammad Shahbaz; Farheen Fatima; Zonaira Nasir; Muhammad Tahir Zaman (Dialogue Social Science Review (DSSR), 2024)
The increasing number of heavy metal pollutants in agricultural soil poses a significant threat to the safety of food and the sustainability of land management, specifically in Europe and Asia. The practice of intensive agriculture has led to a higher probability of soil degradation. Heavy metals like lead, cadmium, and zinc can be stored in the soil, this adversely affects the health of crops and ultimately reaches the food chain, putting a threat to human health. In this context, biochar has become popular due to its high capacity to adsorb toxins, this enables the immobilization of these toxic metals. This investigation explores the role of biochar in alleviating the pollution of heavy metals across diverse agricultural landscapes in Italy, Poland, Norway, Germany, and Belgium, utilizing lattice models to explain the interactions between biochar and heavy metals. The investigation aims to understand the different levels of efficiency of biochar in different soil types, which are affected by factors like the pH of the soil and its organic content, it also highlights the necessity of region-specific strategies in order to maximize the efficiency of biochar. Through case studies of various European agricultural methods, this paper provides empirical evidence of the effectiveness of biochar, specific to the soil restoration efforts of specific individuals. Additionally, practical advice is provided regarding the best way to utilize biochar in agriculture, the purpose of these practices is to support sustainable farming and enhance safety of food. Ultimately, this research contributes to the larger conversation about innovative solutions to soil remediation and the sustainable management of polluted agricultural land, advocating for the incorporation of biochar into conventional soil management methods.